Gender-related differences in clinical presentation, electrocardiography signs, laboratory markers and outcome in patients with acute pulmonary embolism - Obradovic, Slobodan D; Džudović, Boris; Rusović, Siniša; Subota, Vesna; Obradović, Dragana (Vojnosanitetski pregled, 2017)
Background/Aim. Acute pulmonary embolism (PE) is a potentially life threating event, but there are scarce data about gender-related differences in this condition. The aim of this study was to identify gender-specific differences in clinical presentation, the diagnosis and outcome between male and female patients with PE. Methods. We analysed the data of 144 consecutive patients with PE (50% women) and compared female and male patients regarding clinical presentation, electrocardiography (ECG) signs, basic laboratory markers and six-month outcome. All the patients confirmed PE by visualized thrombus on the multidetector computed tomography with pulmonary angiography (MDCT-PA), ECG and echocardiographic examination at admission. Results. Compared to the men, the women were older and a larger proportion of them was in the third tertile of age (66.0% vs 34.0%, p = 0.008). In univariate analysis the men more often had hemoptysis [OR (95% CI) 3.75 (1.16–12.11)], chest pain [OR (95% CI) 3.31 (1.57–7.00)] febrile state [OR (95% CI) 2.41 (1.12–5.22)] and pneumonia at PE presentation [OR (95% CI) 3.40 (1.25–9.22)] and less likely had heart decompensation early in the course of the disease [OR (95%CI) 0.48 (0.24–0.97)]. In the multivariate analysis a significant difference in the rate of pneumonia and acute heart failure between genders disappeared due to strong influence of age. There was no significant difference in the occurrence of typical ECG signs for PE between the genders. Women had higher level of admission glycaemia [7.7 mmol/L (5.5–8.2 mmol/L) vs 6.9 mmol/L (6.3–9.6 mmol/L), p = 0.006] and total number of leukocytes [10.5 ´ 109/L (8.8-–12.7 ´ 109/L vs 8.7 ´ 109/L (7.0–11.6 ´ 109/L)), p = 0.007]. There was a trend toward higher plasma level of brain natriuretic peptide in women compared to men 127.1 pg/mL (55.0–484.0 pg/mL), p = 0.092] vs [90.3 pg/mL (39.2–308.5 pg/mL). The main 6-month outcomes, death and major bleeding, had similar frequencies in both sexes. Conclusion. There are several important differences between men and women in the clinical presentation of PE and basic laboratory findings which can influence the diagnosis and treatment of PE.